Needs assessment and development of a freshman library orientation program for the Philippine Women's University with a survey of orientation programs of selected Metro Manila academic libraries - Borja, Clarita C.; Hidalgo, Namnama P.; Buenrostro, Juan Jr. C. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1988)
The study is an attempt to 1) identify theories, concepts, and principles and describe current practice of library orientation programs (LOPs) in college and university libraries; 2) identify the information needs of PWU Freshmen students which should be provided through library orientation program; and 3) design and develop a library orientation program for the Philippine Women's University.
The descriptive survey method was used in the study. Data were gathered through two structured questionnaires. The first questionnaire was accomplished by twenty-one chief and/or university librarians of the university main libraries, the college librarians, and other college and/or university personnel directly involved in conducting the LOP of their respective schools. The second questionnaire was answered by 145 freshmen and transferees students of the Philippine Women's University during the first semester of School Year 1987-1988.
It was found that the selected college and university libraries have conducted LOPs since their establishment or since 1976. Eleven have done so during the Academic Year 1987-1988. Seventeen out of the twenty one libraries conducted LOPs in the last five years.
Most of the schools publicize their LOPs although four have failed to do so. Publicity activities generally involved posting announcements in bulletin boards, distributing printed programs, and through announcements to faculty members, department chairmen and deans.
About half of the respondents schedule LOPs by appointment or by arrangement and six schools or 28.57 percent schedule LOPs individually, depending on questions asked by the students at the charging desk and on the spot requests.
The usual type of LOP used by the librarians is the course-related instructions usually in cooperation with the faculty handling English classes.
It was also found out that the usual methods used in giving LOP are group tour, instructional aids, handouts, self-paced tour, library lecture, classroom lecture, audio-visual production, programmed instruction and workbooks. Library orientation programs take from half an hour to two hours with one hour as the modal length.
Majority of the respondents indicate that the chief and/or university librarian conducts most or all of the LOP, followed by the reference librarian and the assistant chief/university librarian, and teachers of English ranked fourth among personnel who conduct LOPs.
The most effective features of LOP are those on rules and regulations, library tour, and slide presentation while the weakest or least effective features of LOP were almost similar to the features which were perceived to be strongest.
Likewise, the LOP needs assessment in PWU, majority of the freshmen students of the PWU are aware and participated in the LOP and the rest were not aware of LOP and had not participated in it.
The most frequently mentioned reasons for the usefulness of LOP are that they will be able to use the library wisely and often for their study needs, easily find the reference materials they need, no longer be confused with the different sections of the library and that the LOP disseminates information about the library and its resources and helpful in developing various skills in library utilization which are beneficial to the student.
The best time for conducting the LOP, is at the start of the semester, rather than during the first semester. And students expressed that they need the LOP most when they have to do research or as the need for information arises.
The most useful and valuable feature of LOP expressed by the students is on library rules and regulations and on the topic classification system which was cited as the least effective. LOP is important to library clients to make them effective users of the library.
A video tape recording (VTR) lesson on the Philippine Women's University Libraries was developed in accordance with research results confirming the effectiveness of audio-visual technology.
Mimeographed.
Special Problem (Master of Library Science)--University of the Philippines Diliman
Keywords: College freshman--Library orientation; Philippine Women's University--Freshmen.